Wage subsidies for needy job-seekers and their effect on individual labour market outcomes after the German reforms - Sarah Bernhard; Hermann Gartner; Gesine Stephan (Institute for the Study of Labor (IZA), 2008)
Our paper estimates the average effect of wage subsidies - paid to employers for a limited period of time - on the labour market prospects of needy job-seekers without access to insurance-paid 'unemployment benefit I'. The results show that wage subsidies had large and significant favourable effects: 20 months after taking up a subsidised job, the share of persons in regular employment is nearly 40 percentage points higher across participants. On the whole, groups with particular placement difficulties benefit comparatively more from subsidisation.
urn:nbn:de:101:1-20081126271
Keywords: J68; 330; Wage subsidies; unemployment benefits II for needy job-seekers; evaluation of active labour market programmes; propensity score matching; Lohnsubvention; Arbeitsmarktpolitik; Wirkungsanalyse; Arbeitsuche; Berufliche Integration; Hartz-Reform; Deutschland